YIELD ASSESSMENT OF ELEPHANT FOOT YAM GROWN UNDER MULTILAYER VEGETABLE CROPPING SYSTEM - SINGH, RAJ PAL; S. BHUSHAN,; KUMAR , SANTOSH; SHANKER, RAVI (The Bioscan, 2013)
Field experiments were conducted during the year 2010-11 and 2011-12 to assess the yield and yield attributing characters of elephant foot yam sown with bottle gourd, ridge gourd and bitter gourd under multilayer vegetable cropping system. The days taken to 50 per cent crop (elephant foot yam) emergence (51 days), girth of pseudostem (21 cm), canopy spread (82.4 cm) and yield of corms (376.07 q/ha) was observed highest in the sole crop of elephant foot yam followed by elephant foot yam + bitter gourd with non significant difference and additional yield of bitter gourd (138.8 q/ha). The results clearly indicated that the vegetable bitter gourd can be profitably intercropped with the elephant foot yam.